Performance tendency and morphological investigations of lignocellulosic tea/polyurethane biocomposite materials - EI-Shekeil, Y. A.; Al-Oqla, F. M.; S. M., Sapuan (Springer, 2020)
This work investigates the effect of reinforcing conditions at optimal processing parameters on the morphological properties as well as the mechanical performance of tea/polyurethane bio-composites. Various reinforcing conditions were designed and prepared to reveal the performance tendency and effects of the reinforcing conditions on several composites properties including tensile strength, tensile modulus, elongation to break, in addition to the morphological characteristics of the bio-composites. ASTM standards were considered in performing the performance testing of the composites. Results have demonstrated that only tensile moduli were enhanced with fiber loading, but tensile strength deteriorations occurred. Moreover, this work investigates the similarity in trends for some mechanical behaviors of the composites. Similar trends in reducing the composites strengths as well as the composites strains with increasing fiber loading were detected. This was an evidence of the strong adhesion between the fiber and the polymer in the TWF/TPU composites, which is not necessarily enhancing the composite strength. Such strong adhesion was proved here not necessary to enhance the composite strength. However, the poor filler dispersion due to excessive fiber loading leads to some agglomeration of the fillers as observed by the scanning electron microscopy, which makes it suitable for various industrial applications.